Comitês de Bacias Hidrográficas, representação e participação: desafios e possibilidades à gestão da água e dos recursos hídricos no Brasil - Barbosa, Flávia Darre (2019)
This research discusses about the representation and participation in Management and Planning of Water Resources process in Brazil which is carried out by Hydrographic Basin Committees (CBH’s). The hypothesis of this research was based on the principle: “The Hydrographic Basin Committee, considered in the National Water Resources Policy, is the fundamental collegiate organization of National Water Resources Management System (SINGREH) to ensure the decentralization, effectiveness and democratization of the public management of water resources through the participation and representation of the segments involved in management decisions. The general aim of this study was to understand how representation and participatory management in water resources public policy, based on the CBH, to assess the qualification, representation and participation to strengthen the performance of these entities integrated management of water and water resources in Brazil. To develop this study a systemic-critical approach was adopted. The methodology was based in a bibliographic and documentary research, field survey with interviews (with key actors in water resources management), questionnaires (with state and interstate CBH members), a field study with non-participant observation (CBH Grande Interstate) and participant observation (CBH Turvo Grande / SP). It allowed the identification of the main challenges and possibilities for the representative and participatory management of water resources. The analysis and interpretation of the data was performed with the triangulation of these techniques, associated with progressive theorization. As a result, it was stablished that participation and representation in water resources management in Brazil occur in different stages, with degrees and forms that generate a participatory process composed of social, public and popular participation. The steps of this process in the management of water resources, considering the CBH's occur with the institutionalization of the collegiate, representation of the segments (public power, civil society, water users), the openness to organized civil society participation and participatory practices. The challenges identified are mainly related to the responsibility in representation, information and the need for training on the CBH, as well as, the recognition of the CBH as a fundamental collegiate in water resources management. The conclusion of the study is that the CBH occupies a central position, especially as regards the integration of the different segments involved in the management of this resources. Also, at the deliberations and proposals for management instruments, the proximity to society, expansion of citizenship and management of water.